Pressure tuning of charge ordering in iron oxide - Sergey V. Ovsyannikov; Maxim Bykov; Elena Bykova; Konstantin Glazyrin; Rudra Sekhar Manna; Alexander A. Tsirlin; Valerio Cerantola; Ilya Kupenko; Alexander V. Kurnosov; Innokenty Kantor; Anna S. Pakhomova; Irina Chuvashova; et al. (Nature Communications, 2018)
The charge order transition of commonly known magnetite has only recently been unraveled. Here, the measurement of the low-temperature high-pressure phase diagram of a related material (Fe4O5) elucidates the interplay of average oxidation state and charge-ordering phenomena in the iron oxide family.